2018
DOI: 10.2141/jpsa.0170029
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput Sequencing-based Analysis of the Intestinal Microbiota of Broiler Chickens Fed Genetically Modified Rice Expressing Cry1Ac/Cry1Ab Chimeric <i>Bacillus thuringiensis</i> Protein

Abstract: Many types of Bacillus thuringiensis (Bt)-crops are being grown worldwide, triggering concerns about their potential impact on humans and livestock. To ensure better yield and food safety in China, an attempt has been made to develop Bt-rice targeting a broad range of insects. We aimed to investigate whether feeding genetically modified rice expressing the Bt chimeric Cry1Ac/Cry1Ab protein has any effects on the intestinal microbiota of broilers. Broilers were fed either Bt-rice or its unmodified isogenic pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Czerwinski et al, (2015a), Czerwinski et al, (2015b), Li et al, (2015) and Hameed et al, (2016) also found no negative effect of dietary supplementation of GM maize, rice, soybean meal and sugarcane on hematological, biochemical and histopathological parameters of broilers. Lili et al (2017), McNaughton et al (2014), Halle and Flachowsky (2014) and Sartowska et al (2015) did not observe any adverse effect of feeding transgenic maize, rice, soybean and canola meal on growth performance parameters, carcass traits, nutrient digestibility and intestinal microbiota of broilers, laying hens and quails. Kim (2019) conducted a study on two-day-old broilers for 32 days by using GM maize and soybean simultaneously.…”
Section: Effects Of Feeding With Gm Crops On Poultrymentioning
confidence: 83%
See 1 more Smart Citation
“…Czerwinski et al, (2015a), Czerwinski et al, (2015b), Li et al, (2015) and Hameed et al, (2016) also found no negative effect of dietary supplementation of GM maize, rice, soybean meal and sugarcane on hematological, biochemical and histopathological parameters of broilers. Lili et al (2017), McNaughton et al (2014), Halle and Flachowsky (2014) and Sartowska et al (2015) did not observe any adverse effect of feeding transgenic maize, rice, soybean and canola meal on growth performance parameters, carcass traits, nutrient digestibility and intestinal microbiota of broilers, laying hens and quails. Kim (2019) conducted a study on two-day-old broilers for 32 days by using GM maize and soybean simultaneously.…”
Section: Effects Of Feeding With Gm Crops On Poultrymentioning
confidence: 83%
“…In a series of experimental studies, transgenic soybean meal, maize, canola meal, and rice included separately or simultaneously in the diet did not adversely influence the health status, reproduction traits, and cellular immune response of broiler chickens, laying hens and quails (Korwin-Kossakowska et al, 2016;Sartowska et al, 2015;Halle and Flachowsky, 2014;Gao et al, 2014;Liu et al, 2016;Lili et al, 2017;McNaughton et al, 2014). All the studies are illustrated in Table 3a and 3b.…”
Section: Effects Of Feeding With Gm Crops On Poultrymentioning
confidence: 99%